Jesus-Believing Jews in Australia: Celebrate Messiah as a Case Study - Abramovich, Dvir (Studies in Christian-Jewish Relations, 2011)
This article is the first to examine the messianic Jewish movement, or Jesus-believing Jews, in Australia. It focuses on the Celebrate Messiah organization and its transplanted messianic congregation Beit Hamashiach in Melbourne, Australia. Discussed are Celebrate Messiah's efforts in spreading its message among the Jewish people, and its strained relationship with the local Jewish community. In addition, the essay offers a wide-ranging mapping of the historical emergence of Messianic Judaism, its basic tenets, growth in Israel, as well as the attendant controversy it has generated.